Metabolic activity of intestinal microflora in patients with bronchial asthma - Vladimir Ivashkin; Oxana Zolnikova; Nino Potskherashvili; Alexander Trukhmanov; Natalia Kokina; Alla Sedova; Elena Bueverova (Clinics and Practice, 2019)
The gut microbiota plays the important role to support the immunological tolerance. To study a metabolic activity of the intestinal microflora the 44 patients suffering from bronchial asthma and 17 healthy volunteers were tested. The short-chain fatty acids (SCFA) spectrum was determined using the method of gas-liquid chromatographic analysis. We have detected a significant decrease the total content of the fatty acids in the feces (P<0.001), the absolute concentrations of the individual acids (acetate, propionate, butyrate; P<0.001) and the total content of isoacids (P<0.001) for all of the patients with bronchial asthma in the study, regardless of the phenotype. The anaerobic type of the SCFA spectrum was detected for the majority (83%) of the patients tested. The aerobic type of the SCFA metabolic profile was detected for another part (17%) of the patients tested. Being detected the parameters change could play the principal role as for the bronchial asthma course as to support the organism sensibilisation.